PENGEMBANGAN MEDIA PEMBELAJARAN MATEMATIKA BERBASIS APLIKASI ANDROID LINES AND ANGLES PADA MATERI GARIS DAN SUDUT UNTUK SISWA SMP/MTS - Syifa Ul Fuadi; Lukmanul Akhsani; Makhful Makhful (Jurnal Karya Pendidikan Matematika, 2023)
Today's technology is rapidly advancing. Educators must keep pace with technological progress. The increasing use of smartphones and tablets among students and teachers has spurred the development of more innovative and interactive Android-based learning media. Android-based learning resources are required to assist technological growth, especially for pupils in junior high school. This study aims to develop a valid Android application-based math learning tool and ascertain teachers' and students' reactions. The 4D development model put forth by Thiagarajan (1974) is the basis for this study's research and development (RD) approach. Analysis was completed using student responses, teacher feedback, and expert validation. The findings revealed that the android-based mathematics learning media for seventh-grade students' "lines and angles" topic achieved an average validity score of 4.253, indicating it's highly valid. Teachers' responses had an average score of 4.3, deeming the media very helpful, and student feedback had an average score of 3.87, declaring it helpful. Based on the results, the proposed learning media is feasible as a learning supplement and is worthy of further development.